IMPROVING STUDENT’S SPEAKING SKILL TROUGH COOPERATIVE LEARNING AT 8TH GRADE OF SMPN 1 LEGOK KAB. TANGERANG IN ACADEMIC YEAR 2013/2014 - Euis Yanah Mulyanah (Universitas Muhammadiyah Tangerang, 2016)
Base on the observation on September 16th to May 30th, 2013. Most of the students at the 8th grade SMPN 1 Legok, Kab. Tangerang in academic year 2013/2014 got difficulties in improving their speaking skills. There are several factor that initiate students’ problems such as they are lack of mastering the aspects of oral proficiency; fluency, pronunciation, grammar, comprehension and vocabulary. They reluctant communicate actively and spontaneously with others. Although, they have enough vocabulary to express their ideas and feeling but they do not know how to say and what should they say then. Therefore, the students are still difficult to improve their conversation into great communication. The objective of this research knows the effectiveness of Cooperative Learning in improving students’ speaking skill at the 8th grade SMPN 1 Legok, Kab. Tangerang in academic year 2013/2014. The research methodology was an experimental research, which conducted in two groups; Experimental group (VIII A) and control group (VIII B) as a sample. The VIII A was taught by using Cooperative Learning, while the VIII B was taught without Cooperative Learning. The speaking test gave to gather the data. The test had been tried out to find out validity, reliability, normality and homogeneity. The formula was used to analyze the data was ttest. It was used to determine whether or not there was significance different between students’ score at experiment group and students’ score at control group. After the data had been collect by using test, it was found that t-test was (3,681), whereas the t-table was (2,009) for a = 5 %. The t-test score was higher than t-table, (3,681>2,009). It means that Ha (alternative hypotheses) was accepted while Ho (null hypotheses) was rejected. Since t-test score was higher than t-table, Cooperative Learning was effective in improving students’ speaking skill at the 8th grade students of SMPN 1 Legok, Kab. Tangerang in academic year 2013/2014. Keywords : Cooperative Learning, Speaking Skills